Dangdut Music Therapy Reduces Work Stress in Social Workers: Terapi Musik Dangdut Mengurangi Stres Kerja pada Pekerja Sosial - Novita Ramadhaniaty; Zaki Nur Fahmawati; Ghozali Rusyid Affandi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Work stress is a significant psychological concern within occupational settings, particularly in high-demand human service professions where employees face emotional and physical strain. Specific Background: Social workers at Liponsos experience considerable workload pressures that may lead to elevated stress levels, necessitating practical psychological interventions such as music therapy. Previous studies have suggested that music-based interventions are associated with stress reduction, yet contextual evidence within Indonesian social service institutions remains limited. Knowledge Gap: Empirical data examining dangdut music therapy as an intervention for work stress among social workers in Liponsos settings are scarce, especially using controlled experimental designs. Aims: This study aimed to examine whether dangdut music therapy reduces work stress among social workers at Liponsos. Results: Using a Randomized Control Trial design with pretest and posttest measures, findings indicated a significant decrease in work stress scores in the experimental group receiving dangdut music therapy, while the control group did not demonstrate comparable reduction. Statistical analysis using Paired Sample T-Test and Independent Sample T-Test confirmed significant differences before and after intervention. Novelty: This study provides empirical evidence on the application of dangdut music therapy within a social service institutional context using a controlled experimental approach. Implications: The findings suggest that culturally relevant music therapy may serve as a practical psychological intervention for managing occupational stress among social workers. Highlights: The Intervention Group Demonstrated Significant Score Decreases After Treatment. Statistical Testing Confirmed Differences Between Pretest and Posttest Measurements. Participants Without Treatment Did Not Show Comparable Changes. Keywords: Work Stress, Dangdut Music Therapy, Social Workers, Randomized Control Trial, Occupational Psychology